Kingdom of Morocco : Poverty Update, Volume 2. Annexes - World Bank (Washington, DC, 2013)
According to the 1998-99 Living Standards Measurement Survey conducted in Moroocco, poverty showed a disturbing increase during the 1990s, regardless of how poverty is measured. This report updates the poverty profile for Morocco following the comprehensive approach suggested by the latest World Development Report (see report no. 20888 for an overview of this report). It presents a detailed analysis of 1) Poverty trends in the 1990s (Chapter 2), 2) which factors are key in explaining the observed increase in poverty (Chapter 3), and 3) the support given to the poor by Government intervention (Chapter 4). An overview of the main initiatives taken by the authorities as well as by nongovernmental organizations and private businesses in the late 1990s is presented in the first chapter; their effects, though not captured by the 1998/99 data, are likely to have a significant impact on poverty reduction in the coming years.